Operational Risk Management and Its Impact on the Banking Sector in Nepal - Sayaju, Anjana; Dhakal, Krishna (Khwopa Journal, 2024)
The liberalization and globalization of financial services, with their support from the development of financial technology, have widened and added to the sophistication of banking activities. This study explores the impact of operational risk management in Nepal’s banking sector, drawing upon some principles from operational risk theory. We used structured questionnaires and probability sampling to gather data from 213 banking employees in the Kathmandu valley. The results show that female respondents had better knowledge of operational risk management due to their closeness to the subject. Identification, management, and control of operational risks all together have a significant effect on the operational risk management of Nepalese commercial banks. Systems failure, inability to use new technologies, and lack of management support are obstacles to doing so. In the banking industry, effective management of operational risks is also considered a significant determinant of employee performance. These findings indicate that banks’ implementation of operational risk management can accelerate growth and provide a range of other benefits to their employees, while also demonstrating the bank’s commitment to reducing operational risk. The report concludes by recommending the promotion of employee awareness, training and development programs, and system management in banking to enhance operational risk management.